Assessing the spatial heterogeneity in overall health across the United States using spatial regression methods: The contribution of health factors and county-level demographics. (May 2018) - Tabb, Loni Philip; McClure, Leslie A.; Quick, Harrison; Purtle, Jonathan; Diez Roux, Ana V.
Highlights: Spatial patterning in health outcomes and factors at the US county-level is assessed. Significant spatial heterogeneity exists in health outcomes and factors. Spatial heterogeneity is reduced in health outcomes after consideration of factors. Health outcomes and factors of neighboring counties impact a given county. Associations of health factors with health outcomes varied geographically.